2021
DOI: 10.1002/adfm.202106484
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dimensional Black Phosphorus in Sensor Applications: Advances and Challenges

Abstract: Low-dimensional black phosphorus (LDBP) materials have emerged, with considerable application potential in sensing due to their unique folded structures and remarkable physicochemical properties. These include anisotropies, layer-dependent and tunable band gaps, high carrier mobilities, high current switching ratios, and excellent electron donor capacities. As a type of supporting material that is favorable to signal transmission or reception, LDBP is widely researched in piezoelectric, flexible, chemical, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 123 publications
0
14
0
Order By: Relevance
“…. [39,41] Figure 3d shows the results of the sensing experiment. The curves illustrate the point in time where the device is exposed to 100 ppb NO 2 concentration (the ON state) and when the device is flushed with N 2 to remove NO 2 (the OFF state).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…. [39,41] Figure 3d shows the results of the sensing experiment. The curves illustrate the point in time where the device is exposed to 100 ppb NO 2 concentration (the ON state) and when the device is flushed with N 2 to remove NO 2 (the OFF state).…”
Section: Resultsmentioning
confidence: 99%
“…[ 14,40 ] However, to the best of our knowledge, flexible NO 2 gas sensing devices based on BP have not been reported, due to the poor mechanical properties of BP. To explore the influence of the improved mechanical properties of our intercalated BP, we prepared flexible NO 2 gas sensors [ 41 ] via a simple drop coating method in the glove box. Poly(ethylene terephthalate) (PET) was chosen as the substrate due to its high flexibility and inertness to phosphorus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high preparation cost or refrigeration demand limits the wide application and development of these detectors. In recent decades, low-dimensional materials have attracted substantial attention because of their unique electronic and optoelectronic properties, which promote the development of low-dimensional infrared detectors. Room-temperature blackbody-sensitive photodetectors based on low-dimensional materials have also emerged. As a narrow direct band gap semiconductor, low-dimensional tellurium (Te) exhibits great application potential because of its high mobility, strong light absorption, and good ambient stability. , Wang et al reported that field-effect transistors with ultra-high field-effect mobilities were prepared from solution-grown two-dimensional (2D) tellurium . The work by Amani et al.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional materials with an atomic or molecular thickness (<1 nm) have shown several advantages such as excellent flexibility and mechanical properties, large surface area, low sheet resistance, high carrier mobility, and high biocompatibility required for the construction of wearable biosensors [ 33 , 34 , 35 ]. To date, 2D materials (e.g., graphene [ 36 , 37 ], transition metal dichalcogenides (TMDCs) [ 38 , 39 ], black phosphorus [ 40 , 41 ], and transition-metal carbides (MXenes) [ 42 ]) have been demonstrated with great promise in applications in biosensing technology, including electronic skins [ 43 , 44 , 45 ], contact lenses [ 46 , 47 ], oral sensors [ 48 ], glove sensors [ 49 ], acoustic sensors [ 50 ], and man–machine control systems [ 51 ], as summarized in Figure 1 . Taking the miRNA detection as an example ( Table 1 ), 2D materials have shown excellent properties in the field of biosensors.…”
Section: Introductionmentioning
confidence: 99%